An assessment of the quality of advice provided by patent medicine vendors to users of oral contraceptive pills in urban Nigeria - Ujuju, Chinazo (Dove Medical Press, 2014)
INTRODUCTION: In Nigeria about 50% of oral contraceptive pill users obtain their products from proprietary patent medicine vendors (PPMVs). This group of service providers are poorly trained and have very limited knowledge about contraception. This paper investigated the nature of the advice offered to simulated current and potential users of oral contraceptive pills. The main objective was to assess the nature and quality of advice provided by PPMVs to pill users. METHOD: This study is based on findings from a ‘mystery client’ approach in which three scenarios related to contraceptive pill use were simulated. Each of the 12 mystery clients simulated one of the following three scenarios: new pill users (new to family planning or switching from condom to pills); user seeking a resupply of pills; and dissatisfied pill users intending to discontinue use. Simple random sampling was used to select 410 PPMVs from a total of 1,826 in four states in Nigeria. Qualitative study using in-depth interviews was also conducted. RESULTS: A majority of the PPMVs had pills in stock on the day of the survey and resupplied pills to the clients. PPMVs also understood the reason and importance of referring clients who were new adopters of oral contraceptive methods to a health facility; 30% of the PPMVs referred new adopters to a health facility. However, demand from clients who do not want to go to health care facilities (for various reasons) necessitated the provision of oral contraceptive pills to 41% of the first time users. Some PPMVs prescribed treatment to mystery clients who presented with perceived complications arising from the use of pills, while 49% were referred to a health facility. CONCLUSION: The advice given by PPMVs often falls short of safety guidelines related to the use of oral contraceptive pills. There is a need to continuously update knowledge among the PPMVs to ensure that they provide quality oral contraceptive services as PPMVs bridge the gap between medical experts and users in rural communities.